68Ga-PSMA PET/CT to Distinguish Brain Metastasis of Renal Cell Carcinoma From Radiation Necrosis After Stereotactic Radiosurgery. (November 2021) - Filizoglu, Nuh; Cetin, Ilknur Alsan; Kissa, Tugba Nergiz; Niftaliyeva, Khanim; Ones, Tunc
Abstract : Abstract: Renal cell carcinoma (RCC) is the most common primary malignancy of the kidney. Approximately 35% of patients of RCC presents with distant metastasis at initial evaluation. CT and MRI are the mainstay imaging modalities. Distinguishing radiation necrosis from tumor progression after stereotactic radiosurgery is challenging. Herein, we present a case of a 43-year-old man with RCC who was treated with stereotactic radiosurgery for brain metastases. We want to emphasize the potential value of 68 Ga-PSMA PET/CT imaging in the differential diagnosis and follow-up of tumor progression from radiation necrosis in RCC patients.